2009
DOI: 10.1086/605948
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Respiratory Failure Associated with Respiratory Syncytial Virus Infection in Adults

Abstract: Risk factors associated with respiratory failure during respiratory syncytial virus (RSV) infection have not been assessed in adults. We identified RSV by quantitative reverse transcription polymerase chain reaction in 58 adults during the 2007–2008 winter. Clinical variables and respiratory secretion viral loads were compared in 26 outpatients and 32 inpatients. Cardiopulmonary diseases were more common among inpatients than outpatients (91% vs 31%, P = .0001), whereas mean RSV load was similar. Nasal viral l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 15 publications
1
50
1
3
Order By: Relevance
“…The initial nasal swabs and sputum samples were screened for the presence of RSV RNA by RT-PCR, using a nonquantitative multiplex group A and B RSV-specific RT-PCR assay, as described elsewhere [21,22]. Viral load, recorded as log 10 plaque forming units (PFUs) per milliliter, was determined for all respiratory secretion samples from RSV-infected subjects, using a quantitative RSV group-specific RT-PCR assay, as reported elsewhere [23]. RT-PCR assays for influenza A and B virus were also performed on samples from selected individuals, according to published methods [2].…”
Section: Methodsmentioning
confidence: 99%
“…The initial nasal swabs and sputum samples were screened for the presence of RSV RNA by RT-PCR, using a nonquantitative multiplex group A and B RSV-specific RT-PCR assay, as described elsewhere [21,22]. Viral load, recorded as log 10 plaque forming units (PFUs) per milliliter, was determined for all respiratory secretion samples from RSV-infected subjects, using a quantitative RSV group-specific RT-PCR assay, as reported elsewhere [23]. RT-PCR assays for influenza A and B virus were also performed on samples from selected individuals, according to published methods [2].…”
Section: Methodsmentioning
confidence: 99%
“…Particularly prone to RSV infection are individuals born prematurely, of low birth weight and/or with congenital cardiopulmonary defects, but the majority of serious RSV infections occur among infants with no known risk factors. Individuals with underlying immunodeficiencies (e.g., bone marrow transplant recipients) and the elderly are also at high risk for RSV disease [1821] and HIV-1-infected children shed RSV for remarkably long periods [6,2224]. …”
Section: Respiratory Syncytial Virus: the Diseasementioning
confidence: 99%
“…In a human challenge model using healthy adult volunteers, RSV nasal viral load is closely correlated with clinical symptoms and recovery [18]. Observational studies have shown that RSV viral load is higher and viral shedding more protracted in hospitalised adults compared to outpatients [19], and that a high viral load in hospitalised adults is a risk factor for the development of complications including respiratory failure and the need for mechanical ventilation [20,21]. In human challenge models of asthma and COPD exacerbation, using challenge with rhinovirus, viral load measured in sputum correlates with the degree of host inflammatory response [22,23].…”
Section: Introductionmentioning
confidence: 99%